CCA-Addition Gone Wild: Unusual Occurrence and Phylogeny of Four Different tRNA Nucleotidyltransferases in Acanthamoeba castellanii - Erber, Lieselotte (Mol Biol Evol, 2020)
tRNAs are important players in the protein synthesis machinery, where they act as adapter molecules for translating the mRNA codons into the corresponding amino acid sequence. In a series of highly conserved maturation steps, the primary transcripts are converted into mature tRNAs. In the amoebozoan Acanthamoeba castellanii, a highly unusual evolution of some of these processing steps was identified that are based on unconventional RNA polymerase activities. In this context, we investigated the synthesis of the 3′-terminal CCA-end that is added posttranscriptionally by a specialized polymerase, the tRNA nucleotidyltransferase (CCA-adding enzyme). The majority of eukaryotic organisms carry only a single gene for a CCA-adding enzyme that acts on both the cytosolic and the mitochondrial tRNA pool. In a bioinformatic analysis of the genome of this organism, we identified a surprising multitude of genes for enzymes that contain the active site signature of eukaryotic/eubacterial tRNA nucleotidyltransferases. In vitro activity analyses of these enzymes revealed that two proteins represent bona fide CCA-adding enzymes, one of them carrying an N-terminal sequence corresponding to a putative mitochondrial target signal. The other enzymes have restricted activities and represent CC- and A-adding enzymes, respectively. The A-adding enzyme is of particular interest, as its sequence is closely related to corresponding enzymes from Proteobacteria, indicating a horizontal gene transfer. Interestingly, this unusual diversity of nucleotidyltransferase genes is not restricted to Acanthamoeba castellanii but is also present in other members of the Acanthamoeba genus, indicating an ancient evolutionary trait.